KAJIAN TRANSLASI WAYANG KULIT TRADISIONAL MENJADI FILM ANIMASI DESA TIMUN - Muhammad Fikri Ramadian; Alvanov Zpalanzani Mansoor (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2025)
Timun Village is the first wayang animated film created by Daud Nugraha. Timun Village uses an innovative technique called aniwayang which is inspired by shadow puppets. Desa Timun is unique because it translates traditional shadow puppet shows into a modern animated film. This study aims to find out how the visual translation of traditional wayang kulit into a modern animated film. This study also wants to analyze how the 12 principles of animation are applied to traditional shadow puppets. Based on the analysis, Timun Village made adjustments to the visual aspect by taking into account the existing boundaries of the wayang. By using the aniway technique, you can use various types of shots, add camera movements, and do video editing while applying almost all animation principles. In addition, by adapting animation styles from other countries, it adds a cartoonish impression to shadow puppets.